(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Zinc oxide (nano ZnO) and its counterpart, bulk ZnO, were tested for their effects on thegermination and root growth of eight crops widely utilised in agriculture around the world as sources ofhuman nourishment (Rice, Soybean, Wheat, Cucumber, Sunflower, Lettuce, Maize, and Tomato). NanoZnO and bulk ZnO were tested at concentrations of 0, 2, 10, 20, 50, 200, and 1000 mgL on thegermination rate and root growth of seeds. Root length and root growth were shown to be inhibited,while seed germination was unaffected across the board. Different plant species showed widely varyinglevels of root development inhibition when exposed to metal oxides (nano ZnO and bulk ZnO). All of theplant species evaluated had their root development nearly halted when exposed to nano ZnOsuspensions of 1000 mgL. An IC50 of micro ZnO was determined to be close to 50 mgL for lettuce,cucumber, sunflower, soybean, and tomato, and close to 100 mgL for maize, wheat, and rice. Thissuppression lasted for the entire time the seeds were incubated, not just during the soaking phase. ZnOnanoparticles are more harmful to plants than their counterparts, as shown in the above study. Thus, it isimportant to exercise caution while releasing various items containing micro particles into theenvironment and ecosystem.